PENINGKATAN CITRA DESTINASI PADA WISATA PULAU BOKORI - Rommy Suleman, Nursaban; Nasrul; Hurriyati, Ratih; Amalia Madi, Riski; Ittaqullah, Nurul; Azis Muthalib, Dzulfikri; Rahmayani Ode, Hesty (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service program aimed to enhance the understanding and capacity of stakeholders at the Bokori Island tourist attraction in building a destination image to attract more tourist visits. The method used was participatory training involving 20 participants, utilizing lecture, discussion, and evaluation techniques. Evaluation results indicated a significant improvement in participants' understanding and knowledge of the dimensions of destination image, with an achievement success rate of 85%. This success was supported by factors such as institutional support and participant enthusiasm, although challenges were encountered, including time constraints for some participants due to farming activities. It was concluded that this socialization was effective in improving stakeholder capacity and is expected to contribute to increasing tourist visits to Bokori Island.